PENERAPAN LOCATION BASED SERVICE PADA JURUSAN TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA - Pranatawijaya, Viktor Handrianus; Ronaldo, Deddy; Farhani, Farhani (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
Today, technology is rapidly developing in various elements and kinds of society. Withthe use of technology makes the human mindset that manifests into modernization. Thecampus is one place where the student's education to develop the potential that existed to givebirth to students who are creative, crisis, responsible and moral, especially for students. With theuse of campus introduction technology to students will facilitate the learning process. One of theutilization of technology that is now widely used is android.One of them features Android LBS(Location Based Service) is one of the android features used to describe the technology used tofind the location of the device that the user by utilizing satellite facilities. One of the problems ofthe students is the lack of information about the room at Informatics Engineering, University ofPalangkaraya which relates to the subjects in Informatics Engineering. By utilizing the featureLBS (Location Based Service) on android will answer the existing problems so as to facilitatestudents Engineering University of Palangka Raya.The methodology used in development with Prototype According to Pressman, which hasstages of Communication and early data collection, Quick design, Formation of prototype,Evaluation of prototype, Repair prototype and Final Production. At this stage of analysis is madeFlowchart. At this stage of design also made the creation of Unified Modeling Language (UML).The programming languages used are Java, JSON, SQLite.Application of Space Presentation Faculty of Engineering, University of PalangkarayaBased Location Based Service is designed and built using a Prototype Pressman method, withmap plan designed through Google Earth Pro and Edraw Max 7 which is placed on Google MapAPI where data storage is made in online database Firebase and SQLite as local database withthe development of the application created using Android Studio.Implementation of LocationBased Services on Application of Space Presentation Faculty of Engineering, University ofPalangkaraya Based Location Based Service, which applies to the Google Map API with eachpoint of the room made marker that produces radius which varied where if an application userenter into each radius it will produce notification information room containing the subjects thatare in the room so that the lecture-related rooms can be known.